Comparison of Scar Assessment Score Between Skin Closure with Vicryl Rapide 6/0 and Prolene 6/0 in Cleft Lip Repair - Aziz, Saba; Ahmad, Rao Saood; Ashraf, Muhammad Ayub; Khan, Muhammad Tahir; Jahan , Nuzhat; Ambar, Masooma (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the scar outcomes following cleft lip repair using Vicryl Rapide 6/0 and Prolene 6/0 sutures, using the Vancouver scar scale and to determine which suture type provides superior aesthetic and functional results.Study Design: Case series.Place and Duration of Study: Combined Military Hospital, Lahore Pakistan, from Jan-Dec 2023.Methodology: Twenty patients aged 3 months to 1 year with cleft lips were recruited Over one year using a convenient sampling method. The patients were randomly assigned into two groups: Group A cleft lip repair with Vicryl rapide 6/0, and Group B with Prolene 6/0 suture. The same surgeon performed all procedures. Scar outcomes were assessed at the 1st, 3rd, and 6th months post-surgery using the Vancouver Scar Scale, which evaluated pliability, vascularity, pigmentation, and scar height.Results: Of 20 patients, 45% (n=9) were male and 55% (n=11) were female, with a mean age of 6.40 ± 2.30 months. The suture materials were equally distributed and on a 6-month follow-up for Group-A, had 60% while Group-B had 10% normal Pliability. Vascularity was normal in 60% of Group-A, but only 0% in Group-B.  Group-A showed 80% normal pigmentation and Group-B up to 50%. For scar height, 60% of Group-A scars were flat, compared to only 0% in Group-B.Conclusion: In cleft lip repair, Group-A Vicryl Rapide 6/0 provided better pliability, vascularity and height than Group-B Prolene 6/0, and overall scar appearance however there was no significant difference in pigmentation while reducing the need for suture removal and postoperative complications.